Selection or Network Effects? : Migration Flows into 27 OECD Countries, 1990-2000 - Peder J. Pedersen; Mariola Pytlikova; Nina Smith (Institute for the Study of Labor (IZA), 2004)
Recent migration patterns show growing migration pressure and changing composition of immigrants in many Western countries. During the latest decade, an increasing proportion of the OECD immigrants have been from poor countries, where the educational level of the population is low. The migration patterns may be affected by the relatively generous welfare schemes in most OECD countries, but also network effects and migration policy changes may be important factors behind the observed development. This paper presents empirical evidence on immigration flows into 27 OECD countries during a period of 11 years, 1990? 2000. Using a panel data model, we analyze the determinants of the migration flows. Our results indicate that traditional factors as cultural and linguistic distance are important. Network effects are also strong, but vary between source and destination countries. We do not find clear evidence that selection effects have had a major influence on the observed migration patterns until now. This may partly be explained by restrictive migration policies in many OECD countries which may have dampened the potential selection effects.
Keywords: O15; F22; J61; 330; international migration; selectivity effects; network effects; migration policy; Internationale Wanderung; Einwanderung; Migrationstheorie; Soziales Netzwerk; Schätzung; OECD-Staaten; self selection